Haptic and audio interaction design : 8th International Workshop, HAID 2013, Daejeon, Korea, April 18-19, 2013, Revised Selected Papers - Brewster, Stephen; Oakley, Ian (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 8th International Conference on Haptic and Audio Interaction Design, HAID 2013, held in Daejeon, Korea, in April 2013. The 14 full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on non-intrusive and thermal haptics, new interfaces and interactions, emotion and affect, music, and mobile devices and applications.